Welcoming children into our homes: a theological reflection on adoption - Waters, Brent (Scottish journal of theology, 2002)
The purpose of this essay is to gain some clarity on a theological understanding of adoption as a witness to Christian faith. Contrary to contemporary portrayals of adoption as a reproduction option, the principal thesis of this essay is that adoption is rooted in charity. Adoption signifies a loving act of providing familial care and belonging for a child who would otherwise have none. In developing this thesis, baptism and foster care are examined in regard to Christian claims about the nature of the parent–child relationship. It is argued that since children do not belong to their parents, but are entrusted to their care by God, parental authority is therefore limited. Consequently, the parent–child relationship is embedded within a larger community of faith in which a child is affirmed as both gift and sign of hope.